Institutional Ownership and Profitability Effects on Mining Corporate Social Responsibility - Pikri; Zaenuddin, Achmad; Arrezqi, Misbakhul (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This research was based on the mining companies’ furor poses serious hazards to human health, the environment, and the social communities around mining areas. This study aims to analyze the institutional ownership and profitability on mining corporate social responsibility listed on the Indonesia Stock Exchange (IDX). The research samples were 33 mining companies listed on IDX in 2022 selected using the purposive sampling technique. The analysis model used multiple linear regression analysis. The model analysis method used a partial test (t test), f test, and coefficient of determination test by IBM SPSS 26 program. The result of this study showed that institutional ownership has a negatively significant effect on corporate social responsibility. While profitability has no significant effect on corporate social responsibility.